Strategi Adaptif PT Kulaku Indonesia dengan Pendekatan Ward and Peppard - Permata, Imelda Nova; Pratama, Dicky (MDP Student Conference, 2025)
This research aims to analyze existing information systems, identify potential applications of information technology, and formulate IS/IT strategic plans that support the vision and mission of PT Kulaku Indonesia. The scope includes operational process analysis, implementation of technology trends, cost and benefit investment analysis, and change management in the integration of new technologies. By using the Ward and Peppard Framework, it was concluded that several systems developed were able to increase operational effectiveness through applications that made work easier and supported real-time monitoring, and had value that was ready to compete in the global market. In addition, it is hoped that this application can be expanded to other units, so that it can further improve overall operational efficiency and effectiveness, as well as make a positive contribution to the development of company information technology.